The Influence of Oxide Thickness and Indium Amount on the Analog Parameters of InxGa1-xAs nTFETs - Bordallo, Caio C. M.; Martino, Joao Antonio; Agopian, Paula G. D. [UNESP]; Alian, Alireza; Mols, Yves; Rooyackers, Rita; Vandooren, Anne; Verhulst, Anne S.; Simoen, Eddy; Claeys, Cor; Collaert, Nadine (Ieee-inst Electrical Electronics Engineers Inc, 2017)
The basic analog parameters of three splits of InxGa1 - xAs nTFETs are analyzed for the first time. The first two splits are In0.53Ga0.47As devices with a 3-nm HfO2/1-nm Al2O3 and a 2-nm HfO2/1-nm Al2O3, while the last one is an In0.7Ga0.3As channel with a 3-nm HfO2/1-nm Al2O3 gate. The lowequivalentoxide thicknessimproves the electrostatic coupling, enhancing I-DS, and, consequently, also gm and A(V), especially for higher V-GS. The InGaAs tunnel field-effect transistors (TFETs) show compatible performance with Si TFETs, and have better performance than Si MOSFETs, making them useful for low-power and lowvoltage analog applications. The highest efficiency is found using the combination of a 2-nm HfO2 with In0.53Ga0.47As, due to the 56-mV/dec subthreshold swing obtained. For all splits, the A(V) peak can be related to the V-GS necessary for band-to-band tunneling to become the dominant transport mechanism.
Keywords: Analog parameters; current conduction mechanisms; intrinsic voltage gain; sub-60 mV/dec; tunnel field-effect transistors (TFET)